Efficacy of pelvic floor and core stabilization exercises on urinary incontinence in the postpartum period (Annals of Medical Research, 2024)
Aim: Pelvic floor exercises and core stabilization exercises are effective for urinary incontinence. This study aims to compare the effectiveness of pelvic floor exercises and core stabilization exercises in the treatment of urinary incontinence in women.Materials and Methods: This study was a randomized controlled trial. Forty women 1 to 6 months postpartum were recruited. The postpartum women were randomly divided into three groups: 1) pelvic floor exercises group (PFE); 2) core stabilization group (CS), and 3) control group (C). Pelvic floor muscle exercises were performed 3 times a day (morning, noon, and evening) in 3 different positions (lying on your back, sitting and standing) in the PFE group. Participants performed core stabilization exercises three days a week for 6 weeks in the CS group. Participants did not receive any exercise therapy and continued their routine. Urogenital Distress Inventory (UDI-6), Incontinence Impact Questionnaire (IIQ7) and Incontinence Severity Index (ISI) were used as outcome measurements.Results: A statistically significant difference was observed in all outcome measures in the PFE and CS group (p0.05). There was no significant difference between the outcome measures of the PFE and CS groups except for ISI values (p>0.17). UDI-6 and IIQ7 results in the PFE group improved more than in the CS group. When the PFE and control groups were compared, the PFE group was found to be more effective than the control group in terms of all results (p
Keywords: Postpartum; Incontinence; Pelvic floor; Exercise; Oral glucose tolerance test